What drove income inequality in EU crisis countries during the Great Recession?. (27th January 2021) - Doorley, Karina; Callan, Tim; Savage, Michael
Abstract: Concern about rising inequality in advanced economies increased with the advent of the Great Recession in 2007. Rising unemployment and fiscal consolidation were expected to lead to greater inequality. We examine how the distribution of income in the EU countries that were hardest hit during the recession evolved over this time. We decompose the overall change in income inequality in Portugal, Ireland, Italy, Greece and Spain into parts attributable to changes in employment and wages, demographic changes, discretionary tax–benefit policy and automatic stabilisation effects. We implement this approach using the microsimulation model, EUROMOD, linked to EU‐SILC survey data. Employment and wages were the main drivers of market income inequality increases. Automatic stabilisation effects, particularly through benefits, are found to play an important role in reducing inequality in all of the crisis countries. Their role is less important if we focus on the working‐age population only, due to the limited nature of working‐age benefits in southern European welfare systems. Discretionary policy changes also contributed to reductions in inequality, but to a much lesser extent.